Analisa Semiotik Makna Pesan Iklan Mendorong Mobil Partai Solidaritas Indonesia - Riza Julfaniah (DIGICOM : Jurnal Komunikasi dan Media, 2022)
This study was to determine the meaning of the message conveyed in the PSI Solidaritas Indonesia advertisement version of "push the car". In this study, the researcher wrote the formulation of the problem, namely, what is the meaning of the message contained in the PSI Solidaritas Indonesia version of the "push the car" advertisement?. The theory that refers to this research is Semiotics proposed by Roland Barthes. This study uses a qualitative approach with surgery using Christian Metz's theory to see the reality described. This study also uses Roland Barthes' semiotic theory to see the hidden or invisible reality in the advertisement. In this study, it was concluded that the PSI advertisement version of "pushing a car" contained a myth that existed in Indonesian society, namely mutual cooperation and the motto Bhineka Tunggal Ika, which means that each one is different, but still one. There is no difference between ethnicity and race in Indonesian society.